2020
DOI: 10.1155/2020/2793804
|View full text |Cite
|
Sign up to set email alerts
|

Negligible Effect of Estrogen Deficiency on Development of Skeletal Changes Induced by Type 1 Diabetes in Experimental Rat Models

Abstract: Although postmenopausal osteoporosis often occurs concurrently with diabetes, little is known about interactions between estrogen deficiency and hyperglycemia in the skeletal system. In the present study, the effects of estrogen deficiency on the development of biochemical, microstructural, and mechanical changes induced by streptozotocin-induced diabetes mellitus (DM) in the rat skeletal system were investigated. The experiments were carried out on nonovariectomized (NOVX) and ovariectomized (OVX) control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…However, bone loss (decreases in the ratios of bone mass and bone mineral mass to body mass) led to significant decreases in bone strength. The changes in cancellous bone (mechanical properties of the proximal tibial metaphysis and histomorphometric parameters of the femoral epiphysis and metaphysis) were much more significant than those in compact bone (mechanical properties of the tibial diaphysis), consistent with our previous studies [ 67 , 68 ]. Taking into account the abovementioned relations between osteoporosis and changes in the intestinal microbiome, we studied the effects of LR and AZM on the development of skeletal changes in OVX rats.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, bone loss (decreases in the ratios of bone mass and bone mineral mass to body mass) led to significant decreases in bone strength. The changes in cancellous bone (mechanical properties of the proximal tibial metaphysis and histomorphometric parameters of the femoral epiphysis and metaphysis) were much more significant than those in compact bone (mechanical properties of the tibial diaphysis), consistent with our previous studies [ 67 , 68 ]. Taking into account the abovementioned relations between osteoporosis and changes in the intestinal microbiome, we studied the effects of LR and AZM on the development of skeletal changes in OVX rats.…”
Section: Discussionsupporting
confidence: 92%
“…The histomorphometric measurements of the longitudinal cross-sections of the distal femoral metaphysis and epiphysis were performed on decalcified preparations that were stained with hematoxylin and eosin, prepared as previously described [ 68 , 71 , 72 ], and the measurements of the transverse cross-sections of the femoral diaphysis were made on undecalcified, unstained slides of the femoral diaphysis, prepared as previously described [ 5 , 68 , 71 , 72 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study performed in the rats with type 2 diabetes, a similar pattern was observed—diabetic groups merged together and separated from the nondiabetic cluster [ 103 ]. Moreover, in a different study on rats with type 1 diabetes and estrogen deficiency, a PCA revealed that the effect of estrogen deficiency was negligible and was clearly dominated by the diabetes effect [ 104 ]. Contrary to ANOVA, which makes it possible to compare every single parameter according to quantitative differences, PCA is a qualitative analysis that provides information on the significance of all the measured parameters on total observed variance, highlighting these which affect this variability the most, even if they are not significant in quantitative comparisons [ 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a different study on rats with type 1 diabetes and estrogen deficiency, a PCA revealed that the effect of estrogen deficiency was negligible and was clearly dominated by the diabetes effect [ 104 ]. Contrary to ANOVA, which makes it possible to compare every single parameter according to quantitative differences, PCA is a qualitative analysis that provides information on the significance of all the measured parameters on total observed variance, highlighting these which affect this variability the most, even if they are not significant in quantitative comparisons [ 104 , 105 ]. In the case of the serum, the most important parameters affecting the total variance and cluster formation were glucose and fructosamine, and then MDA, whose high levels were correlated with groups of rats with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%